Pengaruh Stres Kerja Terhadap Kinerja Karyawan di PT Ramayana Lestari Sentosa Cabang Samarinda Central Plaza (Lembaga Pengembangan Kinerja Dosen, 2025)
Work stress is one of the factors that can affect employee performance in a dynamic and high-pressure retail work environment. This study aims to determine the effect of work stress on employee performance at PT Ramayana Lestari Sentosa Tbk Samarinda Central Plaza Branch. The method used is quantitative research with a survey approach involving 127 respondents using a questionnaire. Data were analyzed using simple linear regression and partial tests. The results indicate that work-related stress significantly influences employee performance in a positive direction. This finding suggests that, at certain intensities, work-related stress can act as a positive motivator (eustress) that encourages employees to improve their performance. The implications of these findings highlight the importance of proper stress management to prevent it from escalating into negative pressure that reduces performance. Companies are advised to monitor employee stress levels regularly, provide stress management training, and create a supportive work culture to maintain a balance between work demands and employee well-being.